Improving Vocabulary Skills with Big Book Media in Elementary Students: Meningkatkan Keterampilan Kosakata dengan Media Big Book pada Siswa SD - Sulthoni, Muhammad Hanani Rusydi; Fediyanto, Niko (Indonesian Journal of Education Methods Development, 2024)
General Background: The use of multimedia resources in education has been recognized for its potential to engage young learners and improve language acquisition. Specific Background: Despite the growing interest in innovative teaching materials, there remains limited research on the effectiveness of specific formats, such as Big Book media, in enhancing English language skills among primary school students. Knowledge Gap: Previous studies have not adequately addressed the impact of Big Book media on both learning and writing skills in elementary education contexts. Aims: This study aims to investigate the effectiveness of Big Book media in improving English learning and writing skills among primary school children at SDN X Candi. Results: A quantitative approach employing a Pretest-Posttest Pre-Experimental design was utilized, involving 30 third-grade students (13 boys and 17 girls). Data analysis through a T-test revealed a significant value (2-tailed) of 0.000, indicating a statistically significant improvement in skills after using Big Book media. Novelty: This research contributes new insights into the use of engaging and interactive teaching materials in language education. Implications: The findings suggest that integrating Big Book media in elementary classrooms can significantly enhance students' learning outcomes, supporting its implementation as a valuable educational resource in English language instruction. Highlights: Significant Improvement: The study found a statistically significant enhancement in students' learning and writing skills after using Big Book media. Engaging Features: Big Book media includes singable patterns, bright colors, and attractive visuals that facilitate learning. Quantitative Evidence: A Pretest-Posttest design was employed with 30 third-grade students, demonstrating the effectiveness of the intervention. Keywords: Big Book, English learning, writing skills, primary education, multimedia resources.